Numerical Simulation of Flame Combustion Characteristics of Tail Gas From the Copper Slag Depleted Reduction - Sun, Huiping; Xie, Haojie; Luo, Siyi; Zhang, Weiwei; Zuo, Zongliang; Xianjun, Guo (Frontiers in Energy Research, 2022)
The tail gas with relatively high calorific value, generated from the depleted reduction of copper slag, can be used as fuel for gas turbines. In this study, the flame speed calculation module in PREMIX of CHEMKIN was used to simulate the combustion characteristics of the tail gas after sulfide removal, the effects of equivalence ratio, gas preheating temperature, and the CO2 concentration on the flame propagation speed and the flame combustion temperature were mainly investigated. Results show that the flame propagation speed and the flame combustion temperature increase continuously with the increase in preheating temperature, while it decreases continuously with the increase in CO2 concentration. Additionally, the peak flame combustion temperature appears at an equivalent ratio of 1.1, while the peak flame propagation speed appears at an equivalent ratio of 2.0, which indicates that the flame combustion temperature is not the main factor affecting flame propagation speed for tail gas.